A framework for demonstrating the value of human services - Hiebert, Bryan (2012)
Practitioners and agency managers agree that evaluation is important. However, counsellors seldom evaluate their work with clients in a way that permits making a causal link between the services clients receive and that changes they experience. A framework has been developed for evaluating changes in client knowledge, skills, attitudes, and beliefs and assessing the impact of those changes on the client’s life and on the broader society in which the client lives. The framework also includes a system for tracking the interventions used with a client and the resources needed to successfully implement those interventions. The framework has been used in a variety of counselling situations, educational settings, and guidance initiatives, to provide evidence that there services clients receive are having an impact on the clients life.